Estimating natural rate of interest and equilibrium exchange rate: A case of the Czech Republic - Zdeněk Pikhart; Pavla Froňková (Review of Economic Perspectives, 2019)
Article deals with estimating real natural interest rate and exchange rate to construct monetary conditions index suitable for the Czech open economy. Despite unobservable characteristics of underlying interest rates and exchange rate, the importance of reference indicators for monetary policy is crucial. Proposed monetary condition index in gap form examines monetary impulse on economic and credit cycle in inflation targeting model.
Keywords: D53; E43; F31; 330; Natural Rate of Interest; Equilibrium Exchange Rate; Monetary Conditions Index